Sustainable Tourism Village Based on Community Participation in Lembang Nonongan, North Toraja Regency - Rahman, A. Faidlal; Husin Demolinggo, Ramang; Mularsari, Ardi; Ermawan, Rein (Jurnal Toursci, 2024)
Gluebang Nonongan Tourism Village is a tourist village in the North Toraja district; this tourist village applies community-based tourism or CBT, where the community is the main point in implementing this (CBT) so that the community is optimally empowered in running tourism. The tourist village of Lembang Nonongan has beautiful cultural diversity and is wrapped in beautiful nature, making people's lives very attractive to tourists. A pure life results in the application of community-based tourism in the tourist village of Lembang Nonongan and sees how the participation of the community in this application so that existing problems can be solved. Visible in the area and can be overcome. In this study, the researcher used a research method, namely a qualitative method in which the researcher conducted interviews with related parties such as the head of the culture and tourism department of North Toraja district, the head of the tourism facilities section of the tourism service business, the head of the tourist village, the head of the tourism awareness group and community leaders. In addition, the authors also made observations in the tourist village of Lembang Nonongan and conducted a study of documentation and literature studies to support this research; the analysis was the SWOT analysis used in the discussion of the results of this study.